Performance evaluation of three-phase induction generator operating as grid connected single-phase induction generator using electronic capacitor - Yukhalang, S.; Sawetsakulanond, B.; Kinnares, V. (My University, 2016)
This paper presents performance evaluation of three-phase induction generator operating as a grid connected single phase induction generator using electronic capacitor for variable speed wind energy applications. When the existing delta connected three-phase can operate as a single-phase induction generator by voltage control techniques using electronic capacitor. The proposed converter system for the front end converter, a single-phase full bridge IGBT converter offers bidirectional power flow for the machine operates as a motor and generator modes. For the machine end converter, half bridge IGBT converter offers excitation of the generator. Comparison between one capacitor connecting an external suitable across terminals and electronic capacitor will be given. Performance evaluation like electromagnetic torque, power factor, speed, THDi for both sides of the system for variable speed of a prime mover is given by simulation using MATLAB/Simulink.